2023
DOI: 10.3390/life13020367
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Added during the Differentiation Phase of 3T3-L1 Cells Exerts Anti-Adipogenic Effect by Reducing the Effects of Pro-Adipogenic Prostaglandins

Abstract: A linoleic acid (LA) metabolite arachidonic acid (AA) added to 3T3-L1 cells is reported to suppress adipogenesis. The purpose of the present study aimed to clarify the effects of AA added during the differentiation phase, including adipogenesis, the types of prostaglandins (PG)s produced, and the crosstalk between AA and the PGs produced. Adipogenesis was inhibited by AA added, while LA did not. When AA was added, increased PGE2 and PGF2α production, unchanged Δ12-PGJ2 production, and reduced PGI2 production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…We added PA, SA, and OA, which are abundant and the typical fatty acids in red meat, ALA, which is abundant and the typical fatty acid in vegetable fats, and EPA, a metabolite of ALA, which is abundant and the typical fatty acid in fish meat, to 3T3-L1 cells at the differentiation stage and examined their effect on MDI-evoked adipogenesis during the maturation stage as described in Figure 1 A. AA was used as a positive control because we and other groups reported that AA added during the differentiation stage suppresses adipogenesis evoked by MDI after the maturation stage [ 24 ]. Figure 1 B shows that EPA reduced the intracellular TAG accumulation as an indicator of the level of adipogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We added PA, SA, and OA, which are abundant and the typical fatty acids in red meat, ALA, which is abundant and the typical fatty acid in vegetable fats, and EPA, a metabolite of ALA, which is abundant and the typical fatty acid in fish meat, to 3T3-L1 cells at the differentiation stage and examined their effect on MDI-evoked adipogenesis during the maturation stage as described in Figure 1 A. AA was used as a positive control because we and other groups reported that AA added during the differentiation stage suppresses adipogenesis evoked by MDI after the maturation stage [ 24 ]. Figure 1 B shows that EPA reduced the intracellular TAG accumulation as an indicator of the level of adipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-adipogenic mouse 3T3-L1 cells (JCRB9014; JCRB Cell Bank, Osaka, Japan) were cultured following previously established protocols [ 24 , 25 ]. In summary, 3T3-L1 cells were seeded in 35- or 60-mm dishes containing growth medium (GM) at a density of 1 × 10 5 or 2 × 10 5 , respectively, in the growth stage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As proliferation and the growth of the preadipocytes slow down, phenotypically relevant proteins begin to be expressed in the adipocyte, which might explain the promotion of secretion of leptin by DAT and D + DAT, favoring the growth of lipid droplets and enhancing the maturation of adipocytes after 7 and 14 d of culture. In figures 5 and 6, we can visualize that not all cells showed the typical imprinted ring shape, which is because 3T3-L1 cells accumulate triglycerides when entering a resting state [30], but not all of cells are able to enter the state. The percentage of cells that can enter the resting state is about 10%-50% [31].…”
Section: Discussionmentioning
confidence: 99%